The future of digital platforms: Conditions of platform overthrow. (28th December 2020) - Thomas, Maxime; Le Masson, Pascal; Weil, Benoit; Legrand, Julien
Abstract : Are the digital platforms that we know here to stay? Both empirical insights and theoretical works suggest digital platform stability. Digital platforms such as Airbnb, Netflix and Taobao have experienced tremendous success, and the theoretical works on modularity and multisided markets depict competitive platform landscapes as controlled by a hegemonic platform leader. However, platform history chronicles multiple cases of leadership shifts in platform ecosystems. In this paper, we coin these situations 'platform overthrows' and uncover the relevant strategies for both a challenger to conduct a platform overthrow and for a platform leader to resist it. To do so, we conducted an inductive protocol to reinterpret 27 already published cases of platform overthrow attempts. Our results suggest that, during a platform overthrow attempt, both players articulate functional expansion and technical genericity . Accordingly, we formulate propositions that account for the strategies at play during a platform overthrow attempt. We discuss these results regarding the digital platform literature on competition and conclude that the study of platform overthrow can yield useful insights on the future of digital platforms.